Excellence in the Making - Illinois State Commission on the Improvement of Elementary and Secondary Education, Springfield; Illinois State Commission on the Improvement of Elementary and Secondary Education, Springfield ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
This report represents the efforts of a commission of 20 citizens who were directed by the Illinois General Assembly to identify the principal problems in Illinois' elementary and secondary schools and to recommend specific actions for improving the State's educational program. The commission concluded that student learning should be the foremost criterion for judging the quality of Illinois schools. The State's method of merely implying its priorities and goals with regard to the instructional program is criticized, and it is recommended that the state work with local school districts to establish expectations for student learning, provide expanded learning opportunities, adopt procedures for accountability, and recognize excellence in learning. In the area of personnel, recommendations center on the following needs: (1): strengthening the instructional leadership role of school-level administrators; (2) improving the knowledge, skills, and performance of teachers; (3) providing opportunities for more teacher input into educational decision making; (4) increasing teacher salaries; and (5) improving the processes whereby incompetent teachers and administrators are removed from these positions. It is also recommended that the State play a more direct role in local school management and policy. The necessity of support from parents and the community and the availability of appropriate learning resources are noted. The report concludes that in order to have excellence in Illinois schools, efforts must be concentrated on all areas, recognizing the interdependence of the major parts and attempting to improve each. (RDN)
ERIC Note: For preliminary report, see ED 250 413.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Standards; Accountability; Behavioral Objectives; Dropouts; Educational Improvement; Educational Objectives; Educational Quality; Elementary Secondary Education; Leadership Responsibility; Principals; School Administration; School Effectiveness; School Organization; School Personnel; Staff Development; State School District Relationship; Teacher Evaluation; Teacher Salaries; Excellence in Education -- Illinois; Reports, Evaluative